Biotechnology and Monstrosity: Why We Should Pay Attention to the “Yuk Factor” - Midgley, Mary (The Hastings Center report, 2000)
We find our way in the world partly by means of the discriminatory power of our emotions. The gut sense that something is repugnant or unsavory—the sort of feeling that many now have about various forms of biotechnology—sometimes turns out to be rooted in articulable and legitimate objections, which with time can be spelled out, weighed, and either endorsed or dismissed. But we ought not dismiss the emotional response at the outset as “mere feeling.”